Tumor de klatskin - Granados Quesada, Ronny (2012)
Hilar cholangiocarcinomas are rare neoplasms. Due to their anatomical location, complete surgical resection is technically difficult. It has an annual incidence of 1 in 100.000 habitants. Surgery could be the definitive in early stages, with a 5-years survival of 20%. The majority of pa- tients has advanced disease at diagnoses, with an average survival of 6 to 7 months and usually requires palliative treatment only. Longterm survival is only achieved in patients who have undergone complete resection. Consequently, identification of patients with risk factors, early diagnosis and evaluation of respectability by a surgeon with experience in hepatobiliary surgery are essential